E-Parking Coupon Apps - Goh, Susan; Sidi, Jonathan (Universiti Malaysia Sarawak, (UNIMAS), 2020)
Nowadays, people strives to find a simple way to achieve their goal. In term of car parking fee, the organization gives a great deal of attention when there is a service that provides driver a simple way and saves time for the driver to pay their fee. By using the manual parking coupon system, the driver need to buy their parking coupon at the authorized seller and utilized it as a parking time. The coupon parking indicate that the driver is paid for the parking fee and display it on the dashboard of the car. If the driver need to extend time, they need to walk back to their car to display more parking coupon. This method is wasting the driver’s time. Therefore, the aims of this project is to provide a platform for the driver to pay the parking fee by mobile phone. This interactive and user friendly application aims to help the driver to keep track of their parking session time and reduce time to pay for their parking fee. The objectives of this proposed application is to migrate the existing parking system into computerized parking system. By using the proposed system, driver can avoid their car being penalized by the enforcement officer. The methodology used in this proposed application is the Rapid Application Development (RAD) model. The proposed application is developed based on the collected requirements and design.